Flipaclip Animation Media for Improving Speaking Skills of Elementary School Students - Sidabutar, Yanti Arasi; Hutagalung, Insenalia Sampe Roli (Future Science / FSH-PH Publications, 2022)
This study was structured with the aim of improving the speaking skills of fourth grade students of SD Negeri 091537 Hutabayuraja by using flipaclip animation media based on local wisdom. This type of research is Classroom Action Research (CAR), where the teacher is the implementer of learning while the researcher is the observer. The design of this study uses the Kemmis and Mc. Taggart. This research was conducted in the odd semester of the 2021/2022 academic year, namely in July. The subjects of this study were fourth grade students of SD Negeri 091537 Hutabayuraja which consisted of 20 students. The object of research is students' speaking skills. Data collection techniques using tests and observations. Data were analyzed descriptively and presented in tabular form. The results showed an increase in students' speaking skills, the average value of speaking skills in the first cycle of the first meeting was 65.45 and the second meeting was 68.05. In the second cycle, the average value of speaking skills for the first meeting was 70.65 and the second meeting was 89.5. This means that improving learning outcomes by using flipaclip animation media based on local wisdom can improve the speaking skills of fourth grade elementary school students.